PENGARUH EKSPRESI CD 146 TERHADAP VIABILITAS DAN FUNGSI SEL HUVECs SECARA IN VITRO - Rita Kirana (Jurnal Cakrawala Ilmiah, 2025)
CD146, also known as MCAM (Melanoma Cell Adhesion Molecule), is an adhesion molecule that plays a role in various cellular processes, including intercellular interactions and signal transduction. This study aims to investigate the effect of CD146 expression on viability, proliferation, and several endothelial functions in human umbilical vein endothelial cells (HUVECs) in vitro. HUVECs are a commonly used cellular model to study endothelial function. In this study, CD146 expression in HUVECs was manipulated through transfection of CD146 plasmid for increased expression and siRNA for decreased expression]. Cell viability was measured using MTT assay or CCK-8. Endothelial function was evaluated through monocyte adhesion assay, cell migration assay, and/or measurement of NO production. The results showed that increased CD146 expression significantly increased cell proliferation of HUVECs (p<0.05), while decreased CD146 expression did not significantly affect cell viability. CD146 expression affected monocyte adhesion to HUVECs cells, but did not affect cell migration or NO production. This study demonstrates that CD146 plays a role in the regulation of cell proliferation and monocyte adhesion] on HUVECs cells in vitro. These findings provide new insights into the role of CD146 in endothelial function and potentially have implications in the understanding and treatment of endothelial dysfunction in cardiovascular disease